-2(x+1) + 4 = 6(x-2) + 8
-2x - 2 + 4 = 6x - 12 + 8
-2x + 2 = 6x - 4
-2x = 6x -4 -2
-2x = 6x - 6
-2x -6x = -6
-8x = -6
8x = 6 (The minus signs cancel each other out)
x = 6/8
x = 3/4
2006-11-07 00:12:54
·
answer #1
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
-2(x+1) + 4 = 6(x-2) + 8; multiply everything that is inside the ( ) with what is outside the ( )
The result is -2x - 2 + 4 = 6x - 12 + 8
simplifying some more we get; -2x + 2 = 6x - 4
Moving like terms together and changing signs we get; -2x - 6x = -4 - 2
-8x = -6; dividing both sides by -8
we get; x = 6/8 or 3/4
2006-11-06 13:12:37
·
answer #2
·
answered by india08_30 2
·
0⤊
0⤋
x=4/3
2006-11-06 12:50:51
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
x=3/4
2006-11-06 12:45:15
·
answer #4
·
answered by kiyomidog 2
·
0⤊
0⤋
-2 (x + 1) + 4 = 6 (x - 2) + 8
Distribute
-2x - 2 + 4 = 6x - 12 + 8
Like Terms
-2x + 2 = 6x - 4
Add 4 on each side
-2x + 6 = 6x
Add 2x on each side
6 = 8x
Divide 8 on each side
6/8 = x
Simplify
x = 3/4 or 0.75
2006-11-06 12:51:27
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
3/4
2006-11-06 12:45:25
·
answer #6
·
answered by yourdaddy0 2
·
0⤊
0⤋
x = 3/4 .
2006-11-06 12:50:06
·
answer #7
·
answered by Xx.GiRL.xX 3
·
0⤊
0⤋
First multiply through the parentheses:
-2x - 2 + 4 = 6x - 12 + 8
Now, combine like terms:
-2x + 2 = 6x - 4
Now, add 2x + 4 to both sides:
6 = 8x
Divide both sides by 8:
x = 6/8 = 3/4
2006-11-06 12:47:47
·
answer #8
·
answered by Dave 6
·
0⤊
0⤋
-2(x+1) + 4 = 6(x-2) + 8
-2x - 2 + 4 = 6x - 12 + 8
-2x + 2 = 6x - 4
-2x - 6x = -4 - 2
-8x = -6
x = 6/8 or 3/4
2006-11-06 12:49:47
·
answer #9
·
answered by kezongputi 2
·
0⤊
0⤋
-2(x+1) + 4 = 6(x-2) + 8
-2x + -2 + 4 = 6x - 12 + 8
-2x + 2 = 6x - 4
6 = 8x
6/8 = x
3/4
2006-11-06 13:00:49
·
answer #10
·
answered by K squared 1
·
0⤊
0⤋